Pengabdian Kepada Masyarakat Melalui Hubungan Antara Pengetahuan Tentang Tanaman Obat Keluarga ( TOGA ) Dalam Pemanfaatan Toga Di Puskesmas Tiban Baru - Sri Hainil; Suci Fitriani Sammulia; Suhaera; Aprilya Sri Rhacmayanti (Jurnal Pengabdian Ilmu Kesehatan, 2021)
Health is one of the elements of life in building to realize the complete Indonesian human being. The aim of health development is to increase awareness, will and ability to live healthily for everyone in order to achieve the highest level of public health, as an investment for the development of socially and economically productive human resources. The aim of health services is to achieve a level of public health that satisfies the expectations and needs of the community (consumer satisfaction), through effective services by service providers that satisfy the expectations and needs of service providers (provider satisfaction), in service institutions that are delivered efficiently (institutional satisfaction). . The interaction of the three main pillars of health services in harmony, harmony and balance, is a combination of the satisfaction of the three parties, and this is a satisfactory health service.